Thermal rounding of micron-sized polymer particles in a downer reactor: direct vs indirect heating - Gomez Bonilla, Juan Sebastian; Dechet, Maximilian; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Rapid Prototyping Journal, 2020)
Purpose: The purpose of this paper is to investigate the effect of different heating approaches during thermal rounding of polymer powders on powder bulk properties such as particle size, shape and flowability, as well as on the yield of process. Design/methodology/approach: This study focuses on the rounding of commercial high-density polyethylene polymer particles in two different downer reactor designs using heated walls (indirect heating) and preheated carrier gas (direct heating). Powder bulk properties of the product obtained from both designs are characterized and compared. Findings: Particle rounding with direct heating leads to a considerable increase in process yield and a reduction in powder agglomeration compared to the design with indirect heating. This subsequently leads to higher powder flowability. In terms of shape, indirect heating yields not only particles with higher sphericity but also entails substantial agglomeration of the rounded particles. Originality/value: Shape modification via thermal rounding is the decisive step for the success of a top-down process chain for selective laser sintering powders with excellent flowability, starting with polymer particles from comminution. This report provides new information on the influence of the heating mode (direct/indirect) on the performance of the rounding process and particle properties.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Crystallinity; Particle shape; Particle size; Polymers; Powder flowability; Selective laser sintering; Shape modification; Thermal rounding